A new species of genus Chiloschista (Aeridinae, Vandeae, Epidendroideae, Orchidaceae) from Sumatra Island, Indonesia - Destario Metusala (PhytoKeys)
Chiloschista tjiasmantoi, a new species of epiphytic leafless orchid from the northernmost region of Sumatra Island, Indonesia, is described and illustrated. The flower of this new species is morphologically close to C. javanica, but differs in having oblong-obovate petals, narrowly oblique oblong side lobes with truncate to obtuse apex, and a different shape of lip sac.